2019
DOI: 10.3389/fpsyt.2019.00496
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impact of Parental Post-Traumatic Stress Disorder Symptoms on Mental Health of Their Offspring After the Great East Japan Earthquake

Abstract: Longitudinal studies of the long-term psychological impact of the Great East Japan Earthquake (GEJE) on parents and their children have been limited. The current study aimed to monitor parents’ post-traumatic stress disorder (PTSD) symptoms and behavioral problems among their children over time and to analyze their long-term associations among the survivors of the GEJE. We used data from the GEJE Follow-up for Children study, which recruited 4- to 6-year-old children and those children’s parents immediately af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…This study’s finding that disaster mental health outcomes in children is linked to their parents’ mental health responses has also been found in other studies. Other studies have reported that children’s posttraumatic stress symptoms, other psychiatric symptoms, and difficulties functioning were associated with parental posttraumatic stress symptoms [ 11 , 12 , 31 , 32 , 33 , 34 , 35 , 36 ]. Prior studies have also reported that children’s posttraumatic stress symptoms, school behavior and academic problems, and/or diminished school functioning were associated with parental postdisaster psychopathology [ 13 , 14 , 15 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study’s finding that disaster mental health outcomes in children is linked to their parents’ mental health responses has also been found in other studies. Other studies have reported that children’s posttraumatic stress symptoms, other psychiatric symptoms, and difficulties functioning were associated with parental posttraumatic stress symptoms [ 11 , 12 , 31 , 32 , 33 , 34 , 35 , 36 ]. Prior studies have also reported that children’s posttraumatic stress symptoms, school behavior and academic problems, and/or diminished school functioning were associated with parental postdisaster psychopathology [ 13 , 14 , 15 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have used research designs appropriate to examine causal relationships within the associations between children’s and their parent’s disaster mental health outcomes by collecting prospective longitudinal data on child and parent outcomes. For example, studies have found that parents’ posttraumatic stress symptoms at one year were associated with their children’s psychiatric symptoms approximately three years after the disaster, possibly representing a causal relationship between the earlier parental symptoms and their children’s later symptoms [ 11 , 35 ]. A study of the Great East Japan Earthquake found that parent posttraumatic stress symptoms one year after the disaster were associated with child internalizing behavioral problems at two years, suggesting effects of parents’ reactions on their children [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have pointed out the problem of children’s poor mental health status, but the effects of disasters on their mental health are not always consistent 18 - 21) , and differences in mental health status relative to environmental radiation levels have not been recognized 17) . Also, despite improvements in overall mental health 22) , long-term PTSD after a nuclear disaster and mental health problems associated with evacuation and migration have been pointed out 23) . Furthermore, it should be noted that previous studies have reported that the mental health status of children living in rural areas is worse than that of children in urban areas 24 , 25) .…”
Section: Introductionmentioning
confidence: 99%